An effective program that has been suggested by using smartphones in developing syntax skills for 10th grade students in the capital municipality- Sana'a - Sa'ad, Yahya Ali Yahya (Journal of Educational and Psychological Sciences, 2022)
The main objective point of this search is knowing the effectiveness of the suggested program of using smartphones in enhancing the skills of syntax for 10th grade students in the capital municipality- Sana'a. The researcher has used a semi-empirical curriculum to achieve his aim of the search. The experiment has contained (60) students of 10th grade students in the capital municipality, Sana'a. Those students have been chosen deliberately. This experiment has been divided into two groups; the experimental group that could learn the influenced program that has been recommended by using smartphones and the control group that has studied in the traditional way.The search's tools have represented in the list of the syntax's skills and testing students abilities in syntax. The consequences of the research have proved the statical grades differences between the two groups; the experimental and traditional in distance test and the result went for the experimental group. Besides, that assures the suggesed program of using smartphones has put an influence in enhancing the skills of grammar for 10th grade students. In short, the researcher has recommended the magnificence of applying the techniques of smartphones in learning the Arabic language with its branches and skills. Not only this but also with other subjects. and making a list of rules that lead learning though using the smartphones in order to improve students abilities in high school.
Keywords: program; smartphones; skills of syntax